2006
DOI: 10.1111/j.1525-1497.2006.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and religion in patients with HIV/AIDS

Abstract: BACKGROUND: Spirituality and religion are often central issues for patients dealing with chronic illness. The purpose of this study is to characterize spirituality/ religion in a large and diverse sample of patients with HIV/AIDS by using several measures of spirituality/religion, to examine associations between spirituality/religion and a number of demographic, clinical, and psychosocial variables, and to assess changes in levels of spirituality over 12 to 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
172
4
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(222 citation statements)
references
References 49 publications
20
172
4
26
Order By: Relevance
“…Some interventions focus specifically on the religious [16] or spiritual [3] beliefs and practices that boost coping, but it is likely that the benefits cause a cascade of effects that are manifested both directly and indirectly as indicated in a series of studies conducted by our team that have included demographic, clinical, and self-report data [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…Some interventions focus specifically on the religious [16] or spiritual [3] beliefs and practices that boost coping, but it is likely that the benefits cause a cascade of effects that are manifested both directly and indirectly as indicated in a series of studies conducted by our team that have included demographic, clinical, and self-report data [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…It has been widely used in international studies (Cotton et al 2006;Yohannes et al 2008), but lacks a psychometric evaluation of its Portuguese version, which was translated by MoreiraAlmeida et al, (Moreira-Almeida et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that patients with AIDS experience significantly poorer SWB than patients with cancer and other chronic, terminal illnesses [66]. This may relate to the psychological and spiritual impact of living with an illness that is stigmatized and the effects of blame and guilt on the well-being of patients with HIV infection [67,68]. However, other studies have found no difference in levels of SWB in cancer and HIV populations [69,70].…”
Section: Discussionmentioning
confidence: 93%